Do options-implied RND functions on G3 currencies move around the times of interventions on the JPY/USD exchange rate? - Olli Castrén (European Central Bank (ECB), 2004)
This paper focuses on changes in the currency options market's assessment of likely future exchange rate developments around the times of official interventions in the JPY/USD exchange rate. We estimate the options-implied risk-neutral density functions (RNDs) using daily OTC quotes for options prices with fixed moneyness that avoids the biases that typically characterise the exchange traded price quotes. We find that the episodes of interventions on the JPY/USD exchange rate coincide with systematic changes in all moments of the estimated RNDs on the JPY/USD currency pair, and in several of the moments of the estimated RNDs on the JPY/EUR and USD/EUR currency pairs. In particular, the operations where Japanese yen is sold coincide with a movement in the mean of the RND towards a weaker yen both against the US dollar and the euro, as well as with an increase in implied standard deviations. Prior to the interventions, the RNDs tend to move into opposite direction suggesting, on the average, increasingly unfavourable market conditions and leaning-against-the wind by the Japanese authorities.
Keywords: E58; F31; F33; 330; Foreign exchange market intervention; GARCH; option-implied distributions